Chipless RFID tag by v-shaped multi-resonator for partial discharge-affected equipment identification - Kayser Azam, S.M.; Othman, Mohamadariff; Latef, Tarik Abdul; Illias, Hazlee Azil; Hossain, A K M Zakir; Ababneh, Ahmad A. (2023)
Partial discharge (PD) in insulating materials is a threatening phenomenon for high voltage (HV) equipment. In PD diagnostics, chipless RFID (CRFID) tags have been rarely used despite their recent popularity in so many other sensing applications. So far, only a handful of works have been attempted where CRFID tags are applied to detect PD signals and identify the PD-affected equipment. However, due to the incompatible integration and complicated design of CRFID tags, those attempts have failed to solve the issue of early PD detection while identifying the HV equipment. In this paper, we propose a new CRFID tag that offers a compatible system integration and simple design for the application of early PD detection and HV equipment identification. The proposed tag is designed by using V-shaped multi-resonators on a one-eighth-wave transmission line that is reciprocally bent by a V-shape. With a compact area of 16×15 mm2, the tag is designed to separately exhibit a low-pass response in the ultra-high frequency (UHF) range for PD detection and a multi-resonating response within 2.86-5.27 GHz frequencies for HV equipment identification purposes. Our designed tag offers an encoding capacity of 12 bits, a high bit density of 5 bits/cm2, and a spectral density of 4.98 bits/GHz. We expect the proposed tag will bring a promising solution to overcome the integration complexity of CRFID tags in UHF sensor-based PD sensing applications.